2009
DOI: 10.4306/pi.2009.6.4.299
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Serum Brain-Derived Neurotrophic Factor Levels in Elderly Korean with Dementia

Abstract: ObjectiveThe primary purpose of this study was to investigate the differences in the serum brain-derived neurotrophic factor (BDNF) level between elderly Korean people over 65 years with and without dementia.Methods171 individuals over 65 years were enrolled in this study. Screening for cognitive impairments was carried out using the Mini-Mental Status Examination-Korean version (MMSE-KC). One hundred thirty-two subjects scored below 1.5 standard deviations (SD) of the mean MMSE-KC score, and these were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 49 publications
6
56
2
Order By: Relevance
“…Another studies have shown BDNF levels diminished in AD patients as compared to controls [32][33][34][35][36][37]. Lee (2009) also observed a BDNF levels decrease in both AD and MCI patients [38]. Other results showed increase in the BDNF levels in these patients.…”
Section: Bdnf and Alzheimer's Diseasementioning
confidence: 97%
“…Another studies have shown BDNF levels diminished in AD patients as compared to controls [32][33][34][35][36][37]. Lee (2009) also observed a BDNF levels decrease in both AD and MCI patients [38]. Other results showed increase in the BDNF levels in these patients.…”
Section: Bdnf and Alzheimer's Diseasementioning
confidence: 97%
“…This indicates that decreased insulin signaling resulting in reduced BDNF production may be a contributing factor in AD development. In accordance, AD patients have decreased serum BDNF concentrations compared to healthy, elderly subjects [237][238][239][240][241] while reduced BDNF levels were associated with decreased cognitive performance in healthy individuals [242].…”
Section: Insulin Signaling In the Brainmentioning
confidence: 80%
“…The results from the previous study, however, were limited by the small number of AD patients assessed (N = 11). Another study found no difference in BDNF levels when comparing severely depressed patients with those not severely depressed [13]. That study compared patients with age associated cognitive decline, MCI and AD and used 20 as the cutoff for severe depression.…”
Section: Discussionmentioning
confidence: 99%
“…In one such study, a negative correlation between BDNF serum concentrations and level of depression as measured by the Geriatric Depression Scale has been reported [12]. In contrast, a study of elderly Korean AD patients found no differences in serum BDNF levels between subjects scoring high on the GDS (≥20) and those scoring low on the GDS [13]. The current study investigated the relationship between serum BDNF concentrations and level of depression as measured by the GDS in a sample of Alzheimer's patients to help clarify this relationship.…”
Section: Introductionmentioning
confidence: 99%